Energy and exergy assessment for a University of Sharjah’s PV grid-connected system based on experimental for harsh terrestrial conditions - Tareq Salameh; Abdul Kadir Hamid; Mena Maurice Farag; Essam M. Abo-Zahhad (Energy Reports, 2023)
Solar PV technology’s growth is fast and widespread in the United Arab Emirates (UAE), even though UAE has harsh climate conditions, ambient temperature, irradiance, and humidity are very high during most of the year. These conditions affect the performance and lifespan of the PV systems installed in the UAE. The current work aims to comprehensively assess the performance of a PV system installed in Sharjah city in UAE in different year seasons. A complete experimental setup for a 2.88 kW PV grid-connected system under the terrestrial conditions of Sharjah city is established. Exergy analysis procedure are performed based on the second law of thermodynamics which presents a different and informative means of evaluating and comparing PV systems reasonably and implicitly. Exergy analysis yields efficiencies that show how nearly actual performance methods recognize more clearly than energy analysis the causes and locations of thermodynamic losses. The results show that January has the highest efficiency while July has the lowest efficiency due to the highest ambient temperature in July. Furthermore, the lowest PV module temperature and highest electrical efficiency obtain at low and high ambient temperatures and highest wind speed. At the same time, the highest electrical power exists at low ambient temperature and the high irradiance value. The highest average PV exergy of 15.34% and lowest average PV exergy of 11.80% were detected in January and July, respectively. The low ambient temperatures in January courses reduced low thermal losses and kept the PV model temperature. However, the low solar radiation limited the conversion yield of the PV system.